Pengaruh Kompensasi, Disiplin Kerja, dan Motivasi Terhadap Produktivitas Kerja Karyawan di PT. Sejahtera Mandiri Sawita Kabupaten Langkat, Sumatera Utara - SEMBIRING, DEO HAGANTA; WIDHIANTHINI, WIDHIANTHINI; YUDHARI, I DEWA AYU SRI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Effect of Compensation, Work Discipline, and Motivation on Manpower Productivity of Employees at PT. Sejahtera Mandiri Sawita, Langkat Regency, North Sumatera Productivity is a description of the ability of workers to produce output.PT. Sejahtera Mandiri Sawita, Langkat Regency, North Sumatera is a company engage in the plantation and processing of palm oil. Howefer, what will be analyzed in this study is the effect of compensation, work discipline, and motivation on the productivity of PT. Sejahtera Mandiri Sawita, Kabupaten Langkat, Sumatera Utara. The purposes of this study: (1) analyze the effect of compensation variable, (2) work discipline, and (3) motivation on employees productivity at PT. Sejahtera Mandiri Sawita, Langkat regency, North Sumatera. This study use primary data were used through direct interviews with 72 respondents from PT. Sejahtera Mandiri Sawita, Langkat regency, North Sumatera with a list of questions that have been prepared. To achive this goal, in this study using a quantitative description method with SEM-PLS. The results of this study indicate that the variables of compensation and motivation have a positive and significant effect on work productivity while work discipline is not significant on the work productivity of employees PT. Sejahtera Mandiri Sawita, Langkat regency, North Sumatera. Suggestions that can be given to the management of PT. Sejahtera Mandiri Sawita, Langkat regency, North Sumatera to pay more attention to the welfare of its employees in providing motivation and improving work discipline as well as providing compensation according to performance to employees can increase their work productivity.